(x-2x)+3(1-4x)-4(1-5x)=2(1-3x)

Simple and best practice solution for (x-2x)+3(1-4x)-4(1-5x)=2(1-3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2x)+3(1-4x)-4(1-5x)=2(1-3x) equation:



(x-2x)+3(1-4x)-4(1-5x)=2(1-3x)
We move all terms to the left:
(x-2x)+3(1-4x)-4(1-5x)-(2(1-3x))=0
We add all the numbers together, and all the variables
(-1x)+3(-4x+1)-4(-5x+1)-(2(-3x+1))=0
We multiply parentheses
(-1x)-12x+20x-(2(-3x+1))+3-4=0
We get rid of parentheses
-1x-12x+20x-(2(-3x+1))+3-4=0
We calculate terms in parentheses: -(2(-3x+1)), so:
2(-3x+1)
We multiply parentheses
-6x+2
Back to the equation:
-(-6x+2)
We add all the numbers together, and all the variables
7x-(-6x+2)-1=0
We get rid of parentheses
7x+6x-2-1=0
We add all the numbers together, and all the variables
13x-3=0
We move all terms containing x to the left, all other terms to the right
13x=3
x=3/13
x=3/13

See similar equations:

| m4=29° | | 25x^2-9=10 | | 3z​−5=−20 | | 2/3x+9=8/3x-16 | | 3(2x-4)+2(3x-2)=2(6x-8) | | 3–9w=-33 | | y=2(-1)=5 | | 4x+4-6x-18=-11 | | -20+18b+20=-12+18b | | 3|6x-12+5=59 | | 10(c+10)=127 | | -8x3x+6)=4-x | | 13y+25=y | | 8r-7=39 | | 3(3y+2)=25 | | 3x-10+4x=-2(x-4)+6 | | 10x+12=8x+48 | | 116=-6d+8 | | 464=-8(6x-2)-8x | | 286=-2-6(-6+6a) | | 40+7r=7r+40 | | -5(9+4a)=5(3+2a) | | 8×(6-3x)-2(x-2)=0 | | (x)/(5)+(2)/(3)=(x)/(6) | | 81=-5(n+3)-7n | | 5(x-2)+x=6(x+13)-4x | | 130=-8-6(-6k+1) | | 5x+15=8x=6 | | 4-2(m-3)=-6m+18 | | 4n-2(1-6n)=94 | | 7x-90=580 | | 10x-2-6x=2(2x+4)-1 |

Equations solver categories